1, 8-Naphthyridine-based boron complexes: visible colorimetric probes for highly selective sensing of phosphoric ion. Issue 35 (26th August 2015) - Wu, Gao Fen; Xu, Qiu Lin; Guo, Lin E.; Zang, Tie Nan; Tan, Rui; Tao, Si Ting; Ji, Jian Fei; Hao, Rui Ting; Zhang, Jun Feng; Zhou, Ying
Graphical abstract: Two 1, 8-naphthyridine-based N, O-chelated boron complexes (1 and 2 ) were designed as novel phosphate ion (Pi) probes, which are based on a methoxy oxalyl group reaction site. These two probes showed high selectivity for Pi detection without interference from ATP, PPi, or other anions. Dramatic color changes from colorless to light yellow were observed by the addition of Pi to solutions of 1 and 2 in DMSO/HEPES buffer (0.02 M, pH 7.4) (V/V = 8:2). This qualitative color shift was accompanied by red-shifts in the UV–vis absorbance spectrum of approximately 43 nm for 1 and 46 nm for 2 . Fluorescence quenching was observed in solutions of 1 ( Φ  = 0.31) and 2 ( Φ  = 0.23) upon addition of Pi. Probes 1 and 2 are the first two 1, 8-naphthyridine-based boron complexes developed which serve as colorimetric probes capable of highly selective detection of Pi over other phosphate-based chemical species including P2 O7 4−, ATP, ADP, AMP, GTP, GDP, GMP, TTP, TDP, TMP, UTP, UDP, and UMP. The in vivo imaging results demonstrate that 1 and 2 are able to permeate into the HeLa cells and Caenorhabditis elegans to detect Pi via a strong fluorescence intensity change. Abstract: Two 1, 8-naphthyridine-based N, O-chelated boron complexes (1 and 2 ) were designed as novel phosphate ion (Pi) probes, which are based on a methoxy oxalyl group reaction site. These two probes showed high selectivity for Pi detection without interference from ATP, PPi, or other anions. Dramatic color changes from colorless to light yellow were observed by addition of Pi to solutions of 1 and 2 in DMSO/HEPES buffer (0.02 M, pH 7.4) (V/V = 8:2). This qualitative color shift was accompanied by red-shifts in the UV–vis absorbance spectrum of approximately 43 nm for 1 and 46 nm for 2 . Fluorescence quenching was observed in solutions of 1 ( Φ  = 0.31) and 2 ( Φ  = 0.23) upon addition of Pi. Probes 1 and 2 are the first two 1, 8-naphthyridine-based boron complexes developed which serve as colorimetric probes capable of highly selective detection of Pi over other phosphate-based chemical species including P2 O7 4−, ATP, ADP, AMP, GTP, GDP, GMP, TTP, TDP, TMP, UTP, UDP, and UMP. The in vivo imaging results demonstrate that 1 and 2 are able to permeate into the HeLa cells and Caenorhabditis elegans to detect Pi via a strong fluorescence intensity change.